2020
DOI: 10.1007/s12633-020-00680-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Lowland Rainforest into Oil-palm Plantations and use of Fire alter Topsoil and Litter Silicon Pools and Fluxes

Abstract: The effects of land use and fire on ecosystem silicon (Si) cycling has been largely disregarded so far. We investigated the impacts of land use and fire on Si release from topsoils and litter of lowland rainforest and oil-palm plantations in Jambi Province, Indonesia. Lower concentrations of Si in amorphous silica (ASi) were found in oil-palm plantation topsoils (2.8 ± 0.7 mg g− 1) compared to rainforest (3.5 ± 0.8 mg g− 1). Higher total Si concentrations were detected in litter from oil-palm frond piles (22.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In batch experiments, larger quantities of Si were released by oil-palm litter (44 ± 12 µg Si g −1 litter) compared to rainforest litter (32 ± 8 µg Si g −1 litter) after 28 h of continuous shaking. This was due to higher Si concentrations in the oil-palm litter (23 ± 5 mg g −1 , in rainforest litter: 13 ± 2 mg g −1 ) [20].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In batch experiments, larger quantities of Si were released by oil-palm litter (44 ± 12 µg Si g −1 litter) compared to rainforest litter (32 ± 8 µg Si g −1 litter) after 28 h of continuous shaking. This was due to higher Si concentrations in the oil-palm litter (23 ± 5 mg g −1 , in rainforest litter: 13 ± 2 mg g −1 ) [20].…”
Section: Introductionmentioning
confidence: 93%
“…In the plant, they detected increasing Si concentrations with oil-palm frond age, indicating Si accumulation over time and immobile behaviour of Si [22]. Von der Lühe et al (2020) [20] found trends of decreasing amorphous silica (ASi, which mainly consists of BSi in topsoils) in topsoils when lowland rainforests were converted to oilpalm plantations on Sumatra, Indonesia. In batch experiments, larger quantities of Si were released by oil-palm litter (44 ± 12 µg Si g −1 litter) compared to rainforest litter (32 ± 8 µg Si g −1 litter) after 28 h of continuous shaking.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Oil-palm plantations are usually cultivated for about 25 years (Corley and Tinker, 2016) after which the oil-palm stem is considered a waste product (Awalludin et al, 2015;Onoja et al, 2019). It used to be common practice to 350 burn the stem, as the ash was regarded to sustain soil fertility (Selamat et al, 2019) by releasing Si and other nutrients into topsoil (von der Lühe et al, 2020;Selamat et al, 2019). Yet, these nutrients, including Si, are released from the ash in such high amounts and so quickly that they are highly susceptible to leaching.…”
Section: Identified Si Storage Cycling and Losses On Smallholder Oil-...mentioning
confidence: 99%
“…It is likely that many nutrients are lost from the system before a new generation of oil palms can take them up. Thus, despite the shortterm fertilizing effect of the ash, this process may enhance nutrient and Si depletion for the long term (von der 355 Lühe et al, 2020). Nowadays, replanting follows a zero-burning policy (Corley and Tinker, 2016) to reduce greenhouse gas emissions, air pollution, and to prevent fires from getting out of control and impacting natural vegetation.…”
Section: Identified Si Storage Cycling and Losses On Smallholder Oil-...mentioning
confidence: 99%